2018
DOI: 10.1155/2018/4785089
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review on the Neuroprotective Mechanisms of Vitexin

Abstract: The neural dysfunction is triggered by cellular and molecular events that provoke neurotoxicity and neural death. Currently, neurodegenerative diseases are increasingly common, and available treatments are focused on relieving symptoms. Based on the above, in this review we describe the participation of vitexin in the main events involved in the neurotoxicity and cell death process, as well as the use of vitexin as a therapeutic approach to suppress or attenuate neurodegenerative progress. Vitexin contributes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Fifteen unreported compounds isolated from the rhizomes of Anemarrhena asphodeloides have anti-inflammatory activities (47). It has been reported and summarized that vitexin and isovitexin could be potential substitute medicines for diversity diseases, and may be adjuvants for stubborn diseases or health products (48, 49). However, the effect of isovitexin on brain disorder associated with neuroinflammation hasn't been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen unreported compounds isolated from the rhizomes of Anemarrhena asphodeloides have anti-inflammatory activities (47). It has been reported and summarized that vitexin and isovitexin could be potential substitute medicines for diversity diseases, and may be adjuvants for stubborn diseases or health products (48, 49). However, the effect of isovitexin on brain disorder associated with neuroinflammation hasn't been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…In the group, where both Pb and Vitexin was concurrently administered, there was a significant improvement in a possible degenerative change and chromatolysis was significantly reduced (Figure 4). As part of previous studies, Vitexin has demonstrated its ability to decrease neuronal cell death [43,44] through a different mechanism and to significantly improve neuronal cell structure and function [24,45]. This result in the Pb+Vitexin group, indicates that the number of healthy neurons in DLPFC will be more than the degenerated ones when compared to Pb group (as Figure 4, 6).…”
Section: Discussionmentioning
confidence: 74%
“…Vitexin is a flavonoid that is extracted from various plants including pearl millet, hawthorn, pigeon pea, mung bean, mosses, Passiflora, bamboo, mimosa, wheat leaves, and chaste berry [21]. Its effects are reported in pharmacological roles range from anti-oxidative anti tumour, anti-viral, anti-inflammatory, anti-bacterial, antihypertensive, antinociceptive, antispasmodic, anti-diabetic, antidepressant, neuroprotective and cognitive improving functions [22][23][24][25][26][27][28]. The contribution of Vitexin to neuroprotection is through counteracting the targets that induce neurodegeneration, such as redox imbalance, neuroinflammation and abnormal protein aggregation, which then lead to a reduction of cognitive or motor impairment [24].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, vitexin has been used as a traditional Chinese medicine for the treatment of a variety of diseases for a long year,13 and previous studies have also shown that vitexin has effective antitumor roles in some other tumors, including colorectal cancer,14 leukemia,15 glioblastoma,16 bladder cancer17 and breast cancer,18 which further supported our research that vitexin had significant antitumor activity. Additionally, vitexin was reported to participate in the main events involved in the process of neurotoxicity 19. Vitexin enhanced the production of neuroprotective factors and reduced neurodegeneration, such as abnormal protein aggregation, neuroinflammation, redox imbalance, etc 19…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, vitexin was reported to participate in the main events involved in the process of neurotoxicity 19. Vitexin enhanced the production of neuroprotective factors and reduced neurodegeneration, such as abnormal protein aggregation, neuroinflammation, redox imbalance, etc 19…”
Section: Discussionmentioning
confidence: 99%